The effectiveness of HIV prevention and the epidemiological context - Grassly Nicholas C.; Garnett Geoff P.; Schwartländer Bernhard; Gregson Simon; Anderson Roy M. (The World Health Organization, 2001)
Planning an intervention to prevent infections with the human immunodeficiency virus (HIV) should be guided by local epidemiological and socioeconomic conditions. The socioeconomic setting and existing public service capacity determine whether an intervention can have a significant outcome in terms of a reduction in a defined risk. The epidemiological context determines whether such risk reduction translates into a measurable impact on HIV incidence. Measurement of variables describing the epidemiological context can be used to determine the local suitability of interventions, thereby guiding planners and policy-makers in their choice of intervention. Such measurements also permit the retrospective analysis of the impact of interventions where HIV incidence was not recorded. The epidemiological context is defined for four different categories of intervention, shown to be effective in lower-income countries by randomized controlled trials. Appropriate indicators for the epidemiological context and methodological guidelines for their measurement are proposed. Their use in the transfer of a successful intervention from one context to another and in scaling up the effort to control HIV infection is explored. These indicators should provide a useful resource for those involved in planning HIV prevention interventions.